Role of β-type natriuretic peptide as predictor of early post-operative outcomes in Chinese patients undergoing anesthesia (Bangladesh Journal of Pharmacology, 2017)
The purpose of the present study was to assess whether pre-operative and post-operative B-type natriuretic peptide (BNP) levels could be used as the predictor of post-operative complications in Chinese patients undergoing elective surgery under general anesthesia. A total of 80 adult patients were analyzed. Blood sample to measure BNP was collected from each patient before and after surgery to assess the relationship of pre-operative BNP with all possible clinical outcomes. Elevated BNP levels were associated with prolonged hospital stay and mortality. Our study results suggested that the high levels of BNP predict the prolong hospital stay, increased mortality, and increased usage of balloon pump. Also results suggested that the BNP is one of the key predictors of early post-operative outcomes in Chinese patients undergoing elective surgery under general anesthesia.